Peran Indonesia Dalam Kerjasama Selatan Selatan dan Triangular - Bulbul Abdurachman; Bagus Mi’raz Prakoso (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2017)
South-South and Triangular Cooperation (SSTC) is not a new issue in international development cooperation. South-South Cooperation itself has a long history and has contributed to the international development half a century. Indonesia itself actively involved in SSTC since the Asian-African Conference (AAC), in 1955, this conference became the starting point of a political movement of the joint development of third world countries to carry out international cooperation. Strengthening the role of Indonesia in SSTC significantly more noticeable with the inclusion of Indonesia as a G20 member, and the change of economic status Indonesia become